PENGARUH PENERAPAN MODEL PEMBELAJARANKOOPERATIFTIPE TEKNIK KANCING GEMERINCING TERHADAP PEMAHAMAN KONSEP MATEMATISSISWAKELAS VIII SMPN 6 LUBUK BASUNG - Junaidi, Satrio; Delsi K, Delsi K; Cesaria, Anna (Pendidikan Matematika, 2014)
ABSTRACTÂ The background of this research is about a low understanding of mathematical concept of studentâs math and a less change they have to be participated toward assignment which is given in learning process The purpose of this research is to know whether the understanding of mathematical conceptwith cooperative learning model Kancing Gemerincing technique will be better than a conventional learning technique toward student grade VIII of Junior High School 6 Lubuk Basung. The kind of this research is experimental research by a random design toward a subject. The population of this research is all of students in grade VIII Junior High School 6 Lubuk Basung academic year 2013/2014 that consists of 4 classes. The technique sampling of this research is collected randomly. In this case, class VIII A is chosen as experiment class and class VIII B is chosen as control class. Therefore, understanding of mathematical concepttest is used as instrument. The kind of test is an essay with 0, 87 test reliability. The technique analysis data is t test one way. Based on the result of testing hypothesis t_tabel=1,645 and t_hitung= 2, 5137 because t_hitung > t_tabel, it means the hypothesis is accepted on real level of Î± = 0, 05. It can be concluded that the understanding concept of studentâs math by applying cooperative learning model Kancing Gemerincing technique is better than a conventional learning technique toward students grade VIII of Junior High School 6 Lubuk Basung.